A pandemic Vibrio parahaemolyticus O3:K6 clone causing most associated diarrhea cases in the Pacific Northwest coast of Mexico - de Jesús Hernández-Díaz, Lucio; Leon-Sicairos, Nidia; Velazquez-Roman, Jorge; Flores-Villaseñor, Héctor; Guadron-Llanos, Alma M.; Martinez-Garcia, J. Javier; Vidal, Jorge E.; Canizalez-Roman, Adrián (Frontiers in Microbiology, 2015)
Between September and October of 2004, more than 1230 cases of gastroenteritis due to pandemic O3:K6 strains of Vibrio parahaemolyticus (V. parahaemolyticus) were reported in the relatively small geographical area of Southern Sinaloa, a state located in Northwest Mexico. Since then, V. parahaemolyticus-associated gastroenteritis cases have gradually increased in prevalence spreading from south to north. The present study conducted an epidemiological surveillance of V. parahaemolyticus strains in both environmental and clinical samples along the Pacific coast of Sinaloa from 2011 to 2013. The genetic relatedness, serotype dominance and antibiotic resistance of isolates were investigated. A total of 46 strains were isolated from environmental samples (e.g., sediment, seawater and shrimp), whereas 249 strains were obtained from stools of patients with gastroenteritis. Nine different O serogroups and 16 serovars were identified. Serovars O3:K6 and O6:K46 were identified in both environmental and clinical strains. Whereas most environmental isolates carried the tdh gene (71.74%, 33/46), only three (6.52%) belonged to pandemic clones (O3:K6, O3:KUT and OUT:KUT). In contrast, 81.1% (202/249) of clinical isolates belonged to pandemic serotypes, with O3:K6 (tdh, toxRS/new, and/or orf8) representing the predominant serovar (97%, 196/202). This prevalence of pathogenic (tdh and/or trh positive) and O3:K6 pandemic V. parahaemolyticus isolates in this study were similar to those found from 2004-2010. As investigated by REP-PCR, genetic lineages of selected O3:K6 strains isolated in this study and some isolated earlier were nearly identical. Antimicrobial susceptibility testing showed that most strains (93.8%) were resistant to ampicillin but sensitive to chloramphenicol (98.8%). Multidrug resistance significantly increased from 8.6% (2004-2010) to 22.93% (2011-2013) (p< 0.05). Our data indicate that pandemic O3:K6 clone has endemically established in the Pacific Coast of Mexico